Application of mutual authentication algorithm on the robust communication protocol between the server and the tag for RFID - Huang, Haolin; Isaeva, Gulmira; lin, Haicai; Huang, Wenya (Edelweiss Applied Science and Technology, 2025)
RFID is an automated identification technology which can be ap- plied to many environments such as factory inventory, supply chain management, and access control, etc. we find that Chang authentication protocol can be easily broken by eavesdropping on the communication between the server and the tag. Therefore, we further propose a robust mutual authentication protocol which is feasible for the low-cost RFID tags. The authentication problem in the proposed system is divided into two parts: tag authentication and reader authentication. In tag authentication, we verify the accuracy of the tag. In reader authentication, we ensure that the reader used to read and communicate with the tag has not been compromised by an attack. This paper introduces a novel RFID authentication system. Authentication is a one-to-one process, and we aim to verify the authenticity of an RFID tag. The proposed system mainly consists of three components: one or more RFID tags, one or more RFID readers, and a backend server responsible for storing data used to authenticate the readers and/or tags. In the proposed protocol, both the tag and the backend server do not update their secret information immediately. Even an adversary interrupts the communication, the backend server still can recognize the tag in the next time. So, the proposed protocol can defeat the denial-of-service attack.The proposed protocol not only can withstand the security flaws of Chang protocol, but also can ensure the properties of use privacy, unlink ability, and substantive privacy.